PEMANFAATAN LATEKS KEBUN SEBAGAI BAHAN TAMBAH PADA CAMPURAN BERASPAL PANAS BERKUALITAS TINGGI DAN EKONOMIS - Madi Hermadi; Yohanes Ronny P, S; Yusef Firdaus; Sugiyono - (Direktorat Bina Teknik Jalan dan Jembatan, 2021)
As the second largest natural rubber producer in the world, each year Indonesia produces 3.5 million tons natural rubber which most of it (85%) is sold (exported) to the international market. Currently its price in international markets is fall, of course Indonesia was greatly affected. In response to this condition, the government encourages the use of local natural rubber, including as an additive of asphalt to produce rubberized asphalt as an asphalt pavement binder. However rubberized asphalt products, produced using current technologies, are still inferior in terms of quality and price when compared to polymer modified asphalt which used imported synthetic polymer (SBS). In response to this, a new technology local natural rubber as a binder of hot mix asphalt was developed. The technology latex (which cheapest natural rubber) to modify petroleum asphalt in hot mix asphalt mixture when mixed in pug mill in AMP (Asphalt Mixing Plan). This study was carried out in the laboratory by testing the properties of asphalt and asphalt mixtures based on SKh-1.6.26 (Ditjen Bina Marga, 2018), then compared with current technologies rubberized asphalt and synthetic polymer modified asphalt. In this way, at a dry rubber content of 4.2% to asphalt, in addition to a cheaper price of 22%-25%, the quality of the rubberized asphalt in the mixture and the quality of its hot mix asphalt produced are also higher.